Effect and safety of immunotherapy among elder patients (age ≥ 65) with recurrent or metastatic nasopharyngeal carcinoma - Rui-Ling Xie; Wu-Lin Cai; Yan-Feng Ouyang; Ye-Hao Zou; Rui Sun (BMC Cancer)
Abstract Background The use of immune checkpoint inhibitors (ICIs) combined with chemotherapy constitutes the first-line treatment for recurrent or metastatic nasopharyngeal carcinoma (RM-NPC). However, elderly patients are underrepresented in the majority of related clinical trials. Patients and methods This retrospective study included RM-NPC patients aged 65 years or older who received immunotherapy between January 2015 and February 2022. Cox regression models were utilized to compare the outcomes. Comorbidity assessments (ACE-27, CCI, and ACCI) were used for the geriatric evaluation. Results Among the 95 of 243 patients included in this analysis (71 men), the median follow-up time was 29.3 months. Patients receiving local therapy had longer progression-free survival (PFS) (HR 0.352; 95% CI: 0.145–0.853; p = .021). No significant differences in survival outcomes or toxicity profiles were observed between age groups or among the ICI agent groups. Conclusions The findings suggest that immunotherapy is efficacious and safe for treating RM-NPC in elderly patients. The combination of ICIs and local therapy significantly prolonged survival and could be an option for this vulnerable population.